Ідентифікація конфігурації проектного середовища та проектів кормозабезпечення сімейних молочних ферм - Тригуба, Анатолій Миколайович; Тригуба, Інна Леонтіївна; Боярчук, Олег Віталійович; Рудинець, Микола Віталійович (НТУ "ХПІ", 2018)
На підставі виконаного аналізу стану молочного тваринництва обґрунтовано потребу реалізації проектів кормозабезпечення сімейних молочних ферм. Розроблено науково-методичні засади та метод ідентифікації конфігурації проектного середовища та проектів кормозабезпечення сімейних молочних ферм, які враховують особливості мінливого проектного середовища. Вибір об‘єктів конфігурації проектів здійснюється на підставі аналізу наявних на вітчизняному ринку ресурсів, зокрема технічного оснащення для виробництва кормів, та фіксування їх параметрів із врахуванням технологічних регламентів на функціонування відповідних систем. На підставі розробленого методу проведено ідентифікацію проектного середовища та об‘єктів конфігурації проектів кормозабезпечення сімейних молочних ферм. Обґрунтовані залежності годинної продуктивності виконання логістичних робіт від сумарної площі вирощуваних кормових культур є підставою для врахування логістичних витрат під час планування проектів кормозабезпечення сімейних молочних ферм.

On the basis of performed analysis of dairy cattle breeding has been substantiated the necessity of feed support projects in family dairy farms. The scientific-methodical principles and the method of projects environment configuration identification of the feed support projects in family dairy farms are created, which take into account the peculiarities of projects environment configuration. The project configuration objects selection is based on analysis of the available resources on the domestic market, in particular, the technical equipment for the feeds production, and fixation of their parameters, taking into account the technological regulations for the relevant systems functioning. On the basis of the developed method, the identification of the project environment and the configurations objects for the feed support of family dairy farms are carried out. The objects configuration project identification of dairy farms feed support is implemented on the basis analysis of the technology market (technical equipment) and their characteristics definition. The collection and processing statistical data of the meteorological station was carried out, which determine the time of start and individual works duration in the projects of forage provision of family dairy farms. Using the public cadastral map of Ukraine, the configuration and area of fields under feed crops were determined. The law of the field areas distribution for the fodder crops cultivation has been established. The dependence between the total area of fields for growing fodder crops and the average distance from them to the fodder yard is substantiated. The hourly productivity dependencies of logistics operations on the total area of cultivated forage crops are substantiated. This is the basis for taking logistic costs into account when planning projects for the provision of family dairy farms. The numerical values of the organizational and technological indicators of the forage feeding of family dairy farms configuration projects are received. This is the basis for project modeling and indicators value definition from the implementation of relevant projects.
Configuration identification of project environment and feed support projects of family dairy farm
Keywords: молочне тваринництво; молочна продукція; технологічно інтегровані системи; коопероване виробництво; конфігурація проектів; management; identification; configuration